The war for Palestine : rewriting the history of 1948 - Rogan, Eugene, 1960-; Shlaim, Avi. (Cambridge ; New York : Cambridge University Press, 2007)
The updated second edition of The War for Palestine presents the genesis of the Arab-Israeli conflict.
Saudi Arabia and the war in Palestine, 1947-48.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Israel-Arab War, 1948-1949.; Arab-Israeli conflict; Israel-Arab War, 1948-1949 -- Historiography; Arab-Israeli conflict -- Historiography; Guerre israélo-arabe, 1948-1949.; Conflit israélo-arabe.; Guerre israélo-arabe, 1948-1949 -- Historiographie; Conflit israélo-arabe -- Historiographie; HISTORY -- General; Arab-Israeli conflict; Arab-Israeli conflict -- Historiography; Historiography; 1948-1949; Electronic book